Arctic cruise tourism and social license to operate: exploring social acceptance and trust in cruise tourism - Ólafsdóttir, Rannveig; Bogadóttir, Ragnheiður; Karkut, Jonathan; Welling, Johannes T.; Tuulentie, Seija; Edvardsdòttir, Anna Guðrún; Pállsdóttir Vang, Elísa; Karlsdóttir, Anna (Journal of Land Use Science)
Expanding debate surrounds the impacts the rapidly increasing volume of cruise ships to the Arctic region are having on local ports and communities. This debate largely centres on the influx of visitors and concern about cultural interaction. This paper evaluates the feasibility of using the concept of Social License to Operate (SLO) in Arctic cruise tourism by identifying how attitudes and perceptions pertain to acceptance and trust. Insights are gathered from both passengers and local stakeholders in Iceland and Faroe Islands. Results reveal cruise companies’ dominance in itinerary planning, with minimal communication among destinations. Economic concerns overshadow collaborative planning, leading to varying levels of acceptance among the diverse stakeholders of cruise tourism. While those benefiting economically support the industry, others express reservations. This dichotomy in opinion regarding acceptance and trust highlights the SLO’s challenges within tourism in general. For SLO to have relevance and legitimacy within cruise tourism, flow and circulation of perspectives is critical. 2024